Absolute film separation of dyes/salts and emulsions with a superhigh water permeance through graded nanofluidic channels. Issue 5 (29th March 2022) - Zhang, Tianmeng; Guo, Ruyong; Ying, Guobing; Lu, Zhiyong; Peng, Chao; Shen, Mingxia; Zhang, Jianfeng
Abstract : Nanofluidic channels constructed by synapse-like PDA on PSM ensure high water permeance and dye rejection in composite films. Different pore gradients in the substrate and functional layers facilitate efficient dye/salt separation. Abstract : The development of multifunctional films with a high permeability has been of great concern for effective separation of complex aqueous contaminants, especially in the face of zero or near-zero release regulations. Inspired by the natural structure of sandy soils, polydopamine-wrapped/connected polypyrrole sub-micron spheres (PPSM) were closely packed onto a polypyrrole-coated bacterial cellulose (PBC) support, by which a new two-layered PBC/PPSM composite film formed with graded nanofluidic channels. Interestingly, after being soaked in complex water environments of ethanol, acids, bases, heat, cold and high salinity, or else bended/folded for more than 10 times, the structure and performance of this film still stayed the same, validating its high structural stability and flexibility. Even in a high salinity environment over seawater, this PBC/PPSM film exhibits a dye-separation capacity of almost 100% with a surprisingly superhigh water permeance over one thousand L h −1 m −2 bar −1, one or two magnitudes higher than that of the related films reported in the literature. Meanwhile, the ability for effective oil–water-separation was also validated. Besides the superhydrophilicity and underwater superoleophobicity, the synapse-like-structure-induced graded nanofluidic channels are also proposed to play a key role for rendering such an outstandingly comprehensive performance of the film by greatly overcoming fluid resistance and reducing permeation viscosity.